Evaluation of Front Line Demonstration on Mustard Crop in Rohtak District of Haryana - Sangwan, Meenakshi; Singh, Jagat; Pawar, Neeraj; Siwach, Meena; Solanki, Y P; karan, Ram (Indian Journal of Extension Education, 2021)
Cluster frontline demonstrations on mustard crop covering 114.4 ha area under mustard using variety RH-Â 0749 were carried out by Krishi Vigyan Kendra at 261 farmersâ€™ fields in Rohtak district of Haryana state during three consecutive kharif seasons 2017-18 to 2019-20. The critical inputs were identified in existing crop production technology through farmers meetings and group discussions. The findings showed significantÂ increase in the average yield of demonstrated plot (12.4%) over the control plot of mustard crop. ConsiderablyÂ lower yield was observed under farmerâ€™s practices because of considerable gap/variation in the extent of adoption of recommended technology. Average extension gap, technology gap and technology index ofÂ mustard crop was found 229 kg/ha, 1423 kg/ha and 40.63 per cent, respectively. Three years average yield, net returns and benefit: cost ratio (BCR) in demonstrated plots came out to be 2076 kg/ha, Rs. 51549 Rs/haÂ and 2.9, respectively which was significantly higher than local check with average yield 1846 kg/ha, net returnsÂ 43366 Rs/ha and BCR 2.74. The higher yield and returns in demonstrations indicated that productivity of mustard at farmersâ€™ fields could be increased by adopting improved technologies. Hence, FLDs showed positiveÂ effects of production and protection technologies in mustard crop.